Development of Indonesia’s Diversity-Based Inclusive Education Measuring Tool. - Isnaini, Nurul; Reza, Faisal Adnan (Universitas Islam Negeri Imam Bonjol Padang, 2024)
Indonesia is a multicultural country with diverse ethnicities, languages and religions, which requires an educational approach that includes multiculturalism and inclusiveness. By promoting inclusiveness and multiculturalism, Indonesia can build a more cohesive society that values diversity. Developing an inclusive education measurement tool is essential to address the above challenges, yet a diversity-based education measurement tool has not been developed. Inclusive education also includes various dimensions: Optimal contact conditions intergroup contact theory, climate of multiculturalism, climate of color blindness, climate of critical consciousness, and climate of polyculturalism. Fifty-two items were administered to 150 teachers in Indonesia. The methods used in this research are quantitative and literature study. The sample in this study was obtained using non-probability sampling method with accidental sampling technique. The results of this study obtained 34 out of 52 items that became the final items with the Likert scaling model which was complemented by Structural Equation Model (SEM) analysis with SmartPLS 4. A total of 34 question items were declared valid because the item had a loading factor value 0.5 and 18 were declared invalid. After all items have a loading factor value ≤ 0.5, the 34 items of the Indonesian diversity-based inclusive education scale can be fully utilized